Fique Fabric: A Promising Reinforcement for Polymer Composites (2018)
A relatively unknown natural fiber extracted from the leaves of the fique plant, native of the South American Andes, has recently shown potential as reinforcement of polymer composite for engineering applications. Preliminary investigations indicated a promising substitute for synthetic fibers, competing with other well-known natural fibers. The fabric made from fique fibers have not yet been investigated as possible composite reinforcement. Therefore, in the present work a more thorough characterization of fique fabric as a reinforcement of composites with a polyester matrix was performed. Thermal mechanical properties of fique fabric composites were determined by dynamic mechanical analysis (DMA). The ballistic performance of plain woven fique fabric-reinforced polyester matrix composites was investigated as a second layer in a multilayered armor system (MAS). The results revealed a sensible improvement in thermal dynamic mechanical behavior. Both viscoelastic stiffness and glass transition temperature were increased with the amount of incorporated fique fabric. In terms of ballistic results, the fique fabric composites present a performance similar to that of the much stronger KevlarTM as an MAS second layer with the same thickness. A cost analysis indicated that armor vests with fique fabric composites as an MAS second layer would be 13 times less expensive than a similar creation made with KevlarTM